Studi Kualitatif Tentang Penerapan Manajemen Keuangan Rumah Tangga dan Gaya Hidup Konsumtif Terhadap Kinerja Prajurit TNI Angkatan Laut di Satuan Kerja Akademi Angkatan Laut - Mohamad Sriyanto; Budy Susetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the implementation of household financial management and consumerist lifestyle, as well as their impact on the performance of the Indonesian Navy soldiers at the Indonesian Naval Academy through a qualitative approach. Using in-depth interviews and focus group discussions (FGD) with several soldiers, this research seeks to uncover their experiences, understanding, and perceptions regarding personal financial management and the influence of consumerist lifestyles on their military performance. The analysis reveals that poor financial management and consumerist behavior negatively affect concentration, motivation, and productivity in carrying out their duties. In contrast, the application of sound financial management and a frugal lifestyle positively contributes to performance enhancement. This study suggests the need for financial training programs and awareness campaigns on the importance of a simple lifestyle to improve the performance of the Indonesian Navy soldiers.